2017
DOI: 10.1017/jns.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Overweight dogs exercise less frequently and for shorter periods: results of a large online survey of dog owners from the UK

Abstract: Canine obesity is now the number one health concern in dogs worldwide. Regular physical activity can improve health, and owners are advised to exercise their dogs on a regular basis. However, limited information exists about associations between overweight status of dogs and walking activity. An online survey was conducted between June and August in 2014, coinciding with the broadcast of a national UK television programme, exploring dog behaviour. Information gathered included signalment, overweight status, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…small, medium or large), according to The UK KC classification ( 4 ) . Unlike for the related papers ( 6 , 7 ) , data from dogs under 2 years of age were eligible for inclusion in the analysis for this study. Outcome variables of interest included: frequency of exercise outside of the home/garden (see categories above); walked once per d or more (yes/no); duration of usual exercise (see categories above); and met UK KC guidelines of exercise for that breed (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…small, medium or large), according to The UK KC classification ( 4 ) . Unlike for the related papers ( 6 , 7 ) , data from dogs under 2 years of age were eligible for inclusion in the analysis for this study. Outcome variables of interest included: frequency of exercise outside of the home/garden (see categories above); walked once per d or more (yes/no); duration of usual exercise (see categories above); and met UK KC guidelines of exercise for that breed (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…no reference to a formal body condition scoring system). The main questions considered in the present study were those relating to undesirable behaviours, whereas the questions involving activity are reported in two associated studies ( 10 , 11 ) .…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, group 2 was initially formed and all dogs in this group were neutered and presented overweight or obese; agreeing with epidemiological studies that evaluated the canine obesity [2,6,8]. Then, to compose group 1, which would represent the control situation, dogs were recruited with ideal BCS and also neutered.…”
Section: Discussionmentioning
confidence: 89%
“…Recent study has reported that factors such as age, neuter status and breed influence weight gain in dogs [8]. Increase in sedentary behavior [17], reduction of metabolic rate [2], composition and function of adipose tissue [26] and genetic predisposition [27] justify obesity in older dogs, neutered and some breeds.…”
Section: Discussionmentioning
confidence: 99%